Pemetaan UMKM Batu Bata Desa Srimulyo Melalui Pendataan dan Digitalisasi Berbasis Sistem Informasi Geografis - Siswanto, Budi; Pamungkas, Pramudya Wahyu; Prihatno, Agus; Safinatunnaja, Sari; Saputra, Reza Kurniawan; Putri, Windy Cahya; Adz Zahra, Dian Eka Febriyanti; Aji Mulia, Muhammad Dias; Mushaffa, Annisa Shafia; Thomas, Matthew Alexender; Henriques, Silveria (DEDIKASI: Community Service Reports, 2024)
One form of service activity in Real Work Lectures (KKN) is by collecting data and digitizing Micro, Small and Medium Enterprises (MSMEs) in the Village. Therefore, research was carried out to optimize the dissemination of information regarding the distribution of brick MSMEs in Srimulyo Village. With this data on the distribution of MSMEs, it is hoped that it will make it easier and faster for people to make decisions by providing map visualizations. The steps for data collection and brick mapping begin with preparing data collection materials in the form of dividing data collection areas to speed up data collection. After that, data collection was carried out on MSMEs by direct observation in the field to find out the distribution points of brick craftsmen. After the data was collected, the data was then summarized and processed using Adobe Illustrator software to obtain an image or map of the distribution of brick production MSMEs in Srimulyo Village. Brick-producing MSMEs in Srimulyo Village are spread across approximately 300 locations in 15 hamlets and 34 Rukun Tangga (RT). The bricks produced by Srimulyo Village are known to have good long-lasting quality because they are made from a mixture of rice fields and alluvial soil, so the products are well known and sold outside Solo Raya.